2018
DOI: 10.1186/s12885-018-4844-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of cancer/testis antigen MAGEC2 expression by TRIM28 in tumor cells

Abstract: BackgroundCancer/testis antigen MAGEC2 (also known as HCA587) is highly expressed in a wide variety of tumors and plays an active role in promoting growth and metastasis of tumor cells. However, little is known for the regulation of MAGEC2 expression in cancer cells.MethodsWestern blotting and quantitative RT-PCR were performed to analyze MAGEC2 expression. Co-immunoprecipitation assay was applied for detecting the endogenous interaction of MAGEC2 and TRIM28 in tumor cells. Overexpression and knockdown assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As a scaffolding protein that forms dimer or trimer or even higher order oligomers, TRIM28-mediated interaction with TRIM24, MDM2 and MAGE-C2 could co-exist in a large complex. As shown, introducing ectopic KRAB domains decreased TRIM28 level, which also brings down the levels of TRIM24 and, potentially, MDM2 ( Supplementary Figure S3F ) or MAGE-C2 ( 40 ). The net result is decreased ubiquitination of p53, and thus increased level of p53 protein (Figure 7C ).…”
Section: Discussionmentioning
confidence: 52%
“…As a scaffolding protein that forms dimer or trimer or even higher order oligomers, TRIM28-mediated interaction with TRIM24, MDM2 and MAGE-C2 could co-exist in a large complex. As shown, introducing ectopic KRAB domains decreased TRIM28 level, which also brings down the levels of TRIM24 and, potentially, MDM2 ( Supplementary Figure S3F ) or MAGE-C2 ( 40 ). The net result is decreased ubiquitination of p53, and thus increased level of p53 protein (Figure 7C ).…”
Section: Discussionmentioning
confidence: 52%
“…First, we found multipleMAGE family proteins (e.g. MAGEC2, MAGEB2, MAGEC1, MAGEB6) with a similar gene expression profile to those inclinical trials (MAGEA1, MAGEA4), which have been reported to be tumor specific [40][41][42] . Second, we find numerous Pregnancy-specific glycoprotein (PSG) genes which fall into the broader category of carcinoembryonic antigens (Supplementary Figure 6A).…”
Section: Bayests Accurately Estimates Tumor Specificity From Multidom...mentioning
confidence: 72%
“…As shown in Figure 5 a, the RNA and protein levels of MAGEC2 were increased when ectopic expression of Trim28 ( Figure 5 a). The previous report demonstrated that MAGEC2 protein stability is dependent on the interaction with TRIM28 [ 40 ]. We transfected the FLAG-MAGEC2 expression vector into HEK293T and performed IP-Western blotting.…”
Section: Resultsmentioning
confidence: 99%